DBS Bank - Ansat, A.; Nurmukhayeva, Zh.; Otesh, Ye.; Yeleukhan, A.; Temirkhan, K. («Академик Е.А. Бөкетов атындағы Карағанды университеті» КЕАҚ баспасы, 2020)
this article deals with implementation of new technologies in banking and financial sector. In this case, good examples of international experience taken into consideration.
Keywords: DBS Bank; fintech; mobile payments; bitcoin; cryptocurrency